A Linear Method for the Recovery of Functions Based on Binary Data Completion - Ligun, A. A.; Shumeiko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We construct a linear recovery method based on binary data completion using the Bessel interpolation formula. We find an asymptotic value of the error of this method, determine its norm, and study its properties.